FORMULATION, IN-VITRO AND IN-VIVO X-RAY EVALUATION OF KOLLIDON® SR MATRIX TABLETS OF DILTIAZEM HCL. - ABHIJIT N. MEREKAR; BHANUDAS S. KUCHEKAR (International Journal of Pharma and Bio Sciences, 2014)
The present study was conducted to investigate the effect of Kollidon®SR at different concentrations on the release of profile of diltiazem hydrochloride from matrix tablets. Matrix-based tablet using different concentrations of Kollidon®SR was developed using direct compression technique to contain 90 mg of Diltiazem HCl. The pre-compression and post compression parameters were evaluated. Formulations were evaluated for the release of Diltiazem HCl over a period of 12 hrs in PH 6.8 phosphate buffer using USP type II dissolution apparatus. Diltiazem HCl and pure Kollidon®SR compatibility interactions was investigated by using Fourier-transform infrared spectroscopy and differential scanning colorimetry .Pre-Compression Studies Like Bulk Density, Tappe Density, Compressibility Index, Hausner Ratio, Angle of Repose are done.Formulation was optimized on the basis of acceptable tablet properties like Hardness, Weight Variation, Friability, Content Uniformity and in vitro drug release. The F2 similarity factor for F5 of 86.50 shows drug release pattern very close to marketed product release profile Similarity factor(f2) for formulation code F5 is 86.50. The In-vivo X-ray studies were carried out to confirm the adherence activity In-vivo in rabbits, the studies showed that polymer utilized for the optimization of the formulation showed the sustaining activity in vivo in rabbit by adhering to various sites in the gastrointestinal tract for the period of 12 hr.. The in vitro release profile and the mathematical models indicate that release of Diltiazem HCl can be effectively controlled from a single tablet using Kollidon® SR matrix system.